2021
DOI: 10.1111/clr.13767
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcome measures following soft‐tissue grafting at implant sites: A systematic review

Abstract: Objectives To review the available literature on patient‐reported outcome measures (PROMs) following soft tissue augmentation at implant sites. Materials and Methods A comprehensive electronic and manual search was performed to identify clinical studies that involved soft tissue augmentation around dental implants and reported PROMs, including post‐operative morbidity, painkillers intake, quality of life, aesthetics and satisfactions. Results Nineteen articles were included in the qualitative analysis. Autogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Minor buccal bone defects result in soft tissue concavities, which can be effectively treated by means of soft tissue augmentation (Cairo et al, 2019; Raghoebar et al, 2021; Tavelli et al, 2021; Thoma et al, 2021). The outcome of soft tissue augmentation is clinically relevant because thicker tissues support peri‐implant health (Thoma et al, 2018; Tavelli et al, 2021) and result in higher patient satisfaction and superior aesthetics (Stefanini et al, 2021). Soft tissue augmentation also seems to favour soft tissue stability in the vertical dimension, regardless of the timing of implant placement (Raghoebar et al, 2021; Seyssens et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minor buccal bone defects result in soft tissue concavities, which can be effectively treated by means of soft tissue augmentation (Cairo et al, 2019; Raghoebar et al, 2021; Tavelli et al, 2021; Thoma et al, 2021). The outcome of soft tissue augmentation is clinically relevant because thicker tissues support peri‐implant health (Thoma et al, 2018; Tavelli et al, 2021) and result in higher patient satisfaction and superior aesthetics (Stefanini et al, 2021). Soft tissue augmentation also seems to favour soft tissue stability in the vertical dimension, regardless of the timing of implant placement (Raghoebar et al, 2021; Seyssens et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these limitations, xenogeneic collagen matrices have been developed (Thoma et al, 2012(Thoma et al, , 2014Rothamel et al, 2014). However, most of the studies included in a recent systematic review showed similar patient-reported outcomes between autogenous grafts and substitutes (Stefanini et al, 2021;Thoma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For type 4 implant placement, STA could better preserve the mid‐facial soft tissue thickness (Raghoebar et al, 2021). However, STA had a limited effect on the interproximal bone level (Fickl et al, 2021) and patient‐reported outcome measures (Stefanini et al, 2021). In the future, studies investigating STA for implants in aesthetic areas should (1) develop validated and reliable sets of clinical outcome measures to comprehensively evaluate the clinical, aesthetic and patient‐reported outcomes of STA; (2) focus on the improvement of grafting materials and surgical techniques, to reduce or avoid the morbidity associated with harvesting autogenous connective tissue (Thoma et al, 2021) and (3) emphasize the diagnosis and prevention of the risk factors for aesthetic failures (Thoma et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…22 Use of autologous graft materials has been associated with increased patientreported pain when compared to the use of allografts and/or xenografts. 22,23 Additionally, the method of harvest of autologous grafts has been associated with changes in postoperative patient pain perception. 24 The perception of postoperative discomfort may have a significant impact on future treatment acceptance, with willingness to retreat gingival grafting sites negatively associated with intraoral treatment areas, size of treated sites, and patientreported postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical outcomes, it is important to assess patient satisfaction and patient‐reported outcomes measures, such as postoperative pain, swelling, bleeding, and overall assessment of healing 22 . Use of autologous graft materials has been associated with increased patient‐reported pain when compared to the use of allografts and/or xenografts 22,23 . Additionally, the method of harvest of autologous grafts has been associated with changes in postoperative patient pain perception 24 .…”
Section: Discussionmentioning
confidence: 99%